Job scheduling considering best-effort and soft real-time applications on non-dedicated clusters - Hanzich, Mauricio (2007)
As Network Of Workstations (NOWs) emerge as a viable platform for a wide range of workloads, new scheduling approaches are needed to allocate the collection of resources from competing applications. New workload types introduce high uncertainty into the predictability of the system, hindering the applicability of the job scheduling strategies. A new kind of parallel applications has appeared in business or scientific domains, namely Soft Real-Time (SRT). They, together with new SRT desktop applications, turn prediction into a more difficult goal by adding inherent complexity to estimation procedures. In previous work, we introduced an estimation engine into our job scheduling system, termed CISNE. In this work, the estimation engine is extended, by adding two new kernels, both SRT aware. Experimental results confirm the better performance of simulated respect to the analytical kernels and show a maximum average prediction error deviation of 20%.